PENGARUH KEEFEKTIFAN PENGENDALIAN INTERN, KEADILAN KOMPENSASI DAN PEMAHAMAN STANDAR AKUNTANSI PEMERINTAHAN TERHADAP INDIKASI TERJADINYA FRAUD PADA PENGELOLA KEUANGAN PADA SATUAN KERJA PEMERINTAH DAERAH (SKPD) PROVINSI SULAWESI TENGAH DENGAN KOMITMEN ORGANISASI SEBAGAI VARIABEL INTERVENING - Hidayat BT, Taufik (Katalogis, 2017)
This study aims to identify and analyze the relationship between direct and indirect between the effectiveness of internal control, equity compensation and understanding of government accounting standards for indications of fraud through the commitment of the organization as an intervening variable. The results showed that the seven hypotheses have met the statistical criteria for the analysis of PLS (Partial Least Squares). Respondents in this study is the head managers, Head of Sub Division of Finance, Treasurer and Treasurer Revenue Expenditure amounted to 140 people from each SKPD and techniques of data collection with questionnaires. The analytical tool used is the analysis of PLS (Partial Least Squares) with the help of statistical program WarpPLS version 2.0. The results showed that the seven hypotheses have met the statistical criteria for the analysis of PLS (Partial Least Squares). The results of this study stated that, directly or indirectly, the effectiveness of internal control, equity compensation and understanding of government accounting standards had a significant influence on the indication of fraud through the commitment of the organization as an intervening variable in financial managers in Central Sulawesi province.